2019
DOI: 10.1016/j.jogc.2018.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Non-use of Contraception by Canadian Youth Aged 15 to 24: Findings From the 2009–2010 Canadian Community Health Survey

Abstract: Objectives: Non-use of contraception is an important contributor to unintended pregnancy. This study assessed non-use of contraception and its determinants among Canadian youth aged 15 to 24.Methods: Data from the 2009-2010 Canadian Community Health Survey respondents aged 15 to 24 were used to identify nonusers of contraception among heterosexual youth who had had intercourse within the previous 12 months, were not pregnant or sterilized, and felt it was important to avoid pregnancy. Sociodemographic, behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Our findings are broadly consistent with that of the Non-Use of Contraception of Canadian Youth in the 2009–2010 Canadian Health Survey ( Dunn et al, 2019 ) which showed that 15% of youth had unprotected sex. It is also in line with previous findings that condom use is lower in the context of sex with regular partners in adults ( Macaluso et al, 2000 ; Fetner et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are broadly consistent with that of the Non-Use of Contraception of Canadian Youth in the 2009–2010 Canadian Health Survey ( Dunn et al, 2019 ) which showed that 15% of youth had unprotected sex. It is also in line with previous findings that condom use is lower in the context of sex with regular partners in adults ( Macaluso et al, 2000 ; Fetner et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Further research is also needed to determine whether youth in this group used other forms of contraception as the use of oral contraception was associated with decreased condom use by youth in the 2009–2010 Canadian Health Survey ( Dunn et al, 2019 ) as well as other studies ( Corbin and Fromme, 2002 ; Parkes et al, 2009 ). Adolescents may think that in the context of romantic relationships where contraception is used, protection is not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, young men and women aged 20 to 24 have the highest rates of chlamydia infections (1627.6 per 100,000) [1]. Youth are also at risk of unplanned pregnancy and encounter barriers to accessing effective contraceptive methods [2]. Many university students are among this high-risk group for acquiring STIs and unplanned pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently a study in Addis Ababa supports this finding (6). Other studies state that when parents have better income they usually follow, support and control their child's which reduces exposure of unintended pregnancy (8,10,(34)(35)(36). This might be due to those whose income is from partners might be influenced or forced by their partners due to economic dependency.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa there is a high incidence of risky sexual behaviors among university Students [9]. Reproductive health-related knowledge gaps among sexually active University female student is an important cause of unintended pregnancy [10][11][12][13]. The outcome of unintended pregnancies is unsafe abortions (3); it is a global social and health burdens [2,3,14].…”
Section: Introductionmentioning
confidence: 99%